Comparison of biostimulation and bioaugmentation techniques for the remediation of used motor oil contaminated soil - Abdulsalam,Surajudeen (2009)
This study was carried out on the bioremediation of used motor oil contaminated soil artificially contaminated to a pollutant level of 40,000ppm using biostimulation and bioaugmentation remediation techniques for 42 days. Four treatment options were investigated in wooden microcosms: Control (T1), water amended (T2), biostimulation (T3) and hybrid of biostimulation and bioaugmentation (T4). The effectiveness of bioremediation processes were monitored using the total petroleum hydrocarbon removal (TPH) and total bacterial count (TBC). T3 had the highest TPH removal rate (69.2±0.05%), followed by T4 (65.2±0.25%) and T2 (58.4±0.5%); the control (T1) had the lowest TPH removal rate (43.2±1.5%). TBC revealed that bioremediation actually took place; T4 had the highest maximum bacterial growth of 9.6E+07CFU/g, followed by T3 (7.2E+07CFU/g), T2 (1.7E+05CFU/g) and T1 (1.65E+05CFU/g). In addition, T3 had the highest metal removal rate (2.172%) and T4 had the lowest metal removal rate (0.203%).